The Citrus Flavanone Naringenin Produces Cardioprotective Effects in Hearts from 1 Year Old Rat, through Activation of mitoBK Channels - Testai, Lara; Da Pozzo, Eleonora; Piano, Ilaria; Pistelli, Luisa; Gargini, Claudia; Breschi, Maria Cristina; Braca, Alessandra; Martini, Claudia; Martelli, Alma; Calderone, Vincenzo (Frontiers in Pharmacology, 2017)
Background and Purpose - Incidence of cardiovascular disorders increases with age, because of a dramatic fall of endogenous self-defence mechanisms and increased vulnerability of myocardium. Conversely, the effectiveness of many cardioprotective drugs is blunted in hearts of 1year old rat. The Citrus flavanone naringenin (NAR) was reported to promote cardioprotective effects against ischemia/reperfusion (I/R) injury, through the activation of mitochondrial large conductance calcium-activated potassium channel (mitoBK). These effects were observed in young adult rats, but no data are available about the possible cardioprotective effects of NAR in aged animals. Experimental Approach- This study aimed at evaluating the potential cardioprotective effects of NAR against I/R damage in 1year old rats, and the possible involvement of mitoBK. Key Results- NAR protected the hearts of 1year old rats in both ex-vivo and in-vivo I/R protocols. Noteworthy, these effects were antagonized by paxilline, a selective BK-blocker. The cardioprotective effects of NAR were also observed in senescent H9c2 cardiomyoblasts. In isolated mitochondria from hearts of 1year old, NAR exhibited the typical profile of a mitoBK opener. Finally, Western Blot analysis confirmed a significant (albeit reduced) presence of BK-forming alpha and beta subunits , both in cardiac tissue of 1 year old rats and in senescent H9c2 cells. Conclusion and Implications - This is the first work reporting cardioprotective effects of NAR in 1year old rats. Although further studies are needed to better understand the whole pathway involved in the NAR-mediated cardioprotection, these preliminary data represent a promising perspective for a rational nutraceutical use of NAR in ageing.